Role of sodium salicylate in Staphylococcus aureus quorum sensing, virulence, biofilm formation and antimicrobial susceptibility - Turner, Adam Benedict; Gerner, Erik; Firdaus, Rininta; Echeverz, Maite; Werthén, Maria; Thomsen, Peter; Almqvist, Sofia; Trobos, Margarita (Frontiers in Microbiology, 2022)
The widespread threat of antibiotic resistance requires new treatment options. Disrupting bacterial communication, quorum sensing (QS), has the potential to reduce pathogenesis by decreasing bacterial virulence. The aim of this study was to investigate the influence of sodium salicylate (NaSa) on Staphylococcus aureus QS, virulence production and biofilm formation. In S. aureus ATCC 25923 (agr III), with or without serum, NaSa (10 mM) downregulated the agr QS system and decreased the secretion of alpha-hemolysin, staphopain A and delta-hemolysin. Inhibition of agr expression caused a downregulation of delta-hemolysin, decreasing biofilm dispersal and increasing biofilm formation on polystyrene and titanium under static conditions. In contrast, NaSa did not increase biofilm biomass under flow but caused a one log10 reduction in biofilm viability on polystyrene pegs, resulting in biofilms being twice as susceptible to rifampicin. A concentration-dependent effect of NaSa was further observed, where high concentrations (10 mM) decreased agr expression, while low concentrations (<=0.1 mM) increased agr expression. In S. aureus 8325-4 (agr I), a high concentration of NaSa (10 mM) decreased hla expression, and a low concentration of NaSa (<=1 mM) increased rnaIII, hla and spa expression. The activity of NaSa on biofilm formation was dependent on agr type and material surface. Eight clinical strains isolated from prosthetic joint infection (PJI) or wound infection belonging to each of the four agr types were evaluated. The four PJI S. aureus strains did not change their biofilm phenotype with NaSa on the clinically relevant titanium surface. Similarly, most wound strains (except agr II) did not change the biofilm phenotype in the 3D collagen wound model. In addition, compared to the control, ATCC 25923 biofilms formed with 10 mM NaSa in the collagen model were more susceptible to silver. It is concluded that NaSa can inhibit QS in S. aureus, decreasing toxin production with certain modulation of biofilm formation. The effect on biofilm formation was dependent on the strain and material surface. It is suggested that the observed NaSa inhibition of bacterial communication is a potential alternative or adjuvant to traditional antibiotics.